Chemoprophylaxis: Boran cattle can be productive under high tsetse challenge - Trail, J.C.M.; Murray, M.; Sones, Keith R.; Jibbo, J.M.C.; Durkin, J.W.; Light, D.E. (1984)
Evaluates the productivity of Boran cattle maintained with chemoprophylaxis in an area of massive Glossina morsitans sub morsitans, G. pallidipes et G. Brevipalpis challenge at Makwaja ranch, in Tanzania and analyses the effect of a chemoprophylactic drug (isometamidium chloride) on cattle productivity.